Lung Cancer: A Literature Review - Yan Efrata Sembiring; Wiwin Is Effendi; Jeffrey Jeswant Dillon; Heroe Soebroto; Dhihintia Jiwangga Suta Winarno; Puruhito Puruhito; I Gusti Agung Made Adnyanya Putra; Abed Nego Okthara Sebayang; Sri Pramesthi Wisnu Bowo Negoro (Jurnal Respirasi, 2023)
Lung cancer is a cancer whose onset starts in the lungs where there is an abnormal cell growth that is very fast and uncontrolled. The abnormal cell growth is triggered by deoxyribonucleic acid (DNA) damage, including deletions in the DNA section, inactivation of tumor suppressor genes, activation of proto-oncogenes to oncogenes, the absence of apoptosis, and the activity of the telomerase enzyme. Lung cancer is initiated by oncogeneous activity and inactivation of tumor suppressor genes. Oncogenes are genes that help cells grow and divide and are believed to cause a person to develop lung cancer. In general, lung cancer is divided into two types, namely non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC). World Health Organization (WHO) classifies lung cancer based on histopathology into 4 major cell types, namely SCLC, NSCLC which includes adenocarcinoma, squamous cell carcinoma (SCC), and large cell carcinoma (LCC). The difference between the two is that SCLC has a higher aggressiveness than NSCLC. Cancer treatment is based on the type, size, location and stage of the cancer, as well as the patient's overall condition.